THE ORIGINS AND FACTORS CONTRIBUTING TO THE DEVELOPMENT OF STOMATOPHOBIA IN CHILDREN. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Dental phobia, or a fear of dental procedures, is one of the most common fears among It is estimated that between 35% and 68% of the global population experience some level of dental anxiety. Delivery of effective dental treatment to a child patient requires thorough knowledge to recognize dental fear and its management by the application of behavioral management techniques. This fear can be particularly intense, leading to a condition known as stomatophobia. Stomatophobia can develop in childhood and continue to affect people throughout their lives.